A systematic review of the clinical use of a single-layer bovine collagen-elastin acellular dermal matrix - David M. Hill (Burns Open)
Introduction: Dermal substitutes have significantly changed the practice of caring for acute and chronic wounds, earning a place on the reconstructive ladder. MatriDerm is a single-layer acellular dermal matrix composed of bovine collagen types I, III, and V with added bovine elastin (CEM). It was developed in the 1990′s, has been commercially available outside of the US since 2005, and received FDA clearance for use in the US in 2021. The objective of this study was to review the published literature to identify an exhaustive list of references describing the clinical use of CEM and summarize the findings. Methods: An extensive search of PubMed and Google Scholar was performed to identify manuscripts describing the clinical use of CEM. Manuscripts were excluded if they were primarily animal models, in vitro studies, reviews, expert opinion articles, or lacked sufficient detail. Google Translate was utilized when necessary. Results: Five hundred and thirty-five manuscripts containing potential details of CEM usage were identified. After exclusions, 128 remained (13 randomized control trials, 30 cohort studies, and 85 case series/reports) originating from 38 countries, including nearly 2,600 clinical cases dating back to 1995. Cases varied considerably and included: burns, acute traumatic injuries, chronic wounds, and soft tissue reconstruction in patients ranging from pediatric to the elderly. A single-stage procedure (CEM placement and covered with an autograft in the same procedure) was the most reported technique, but autograft application in a later procedure was also reported. Negative pressure wound therapy was utilized in many of the studies. Study endpoints varied widely and included graft take, several objective scar scales, cutometer/durometer measures, range of motion, patient satisfaction scores, and histology. Conclusions: There is an extensive body of global literature dating back to the 1990’s documenting CEM successfully utilized as a dermal matrix for a vast number of patients and indications.